Discontinuous Boundary Value Problems with Retarded Argument and Eigenparameter-Dependent Boundary Conditions - Akgun, Fatma Aydin; Bayramov, Azad; Bayramoglu, Mehmet (SPRINGER BASEL AG, 2013)
In this paper we study the asymptotic formulas for the eigenvalues and corresponding eigenfunctions of discontinuous boundary value problems with retarded argument and eigenparameter-dependent boundary conditions.
Keywords: Retarded argument; eigenparameter; transmission conditions and discontinuous boundary value problems; STURM-LIOUVILLE PROBLEMS; Mathematics